Varicella Zoster encephalitis versus Acyclovir toxicity: Diagnostic dilemma and Treatment challenge in an ESRD patient - Mahbub, Tania; Haque, Elena; Akter, Salina; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2020)
Abstract Not Available Bangladesh Crit Care J March 2020; 8(1): 58-60